Respostas
respondido por:
5
oi
a) 4x²-36=0
onde:
a=4
b=-36
c=0
Δ=b²-4..c
Δ=(-36)²-4.4.0
Δ=1296-16.0
Δ=1296
x=-b+-√Δ/2a
x=+36+-√1296 /2.4
x=36+-36/8=
x1=36+36/8=
x1=9
x2=36-36/8
x2=0
solução: 0,9
b) 7x²-21=0
onde:
a=7
b=0
c=-21
b é igual a zero então :
x1= √3
e
x2= -√3
solução: -√3,√3
beijãoo
a) 4x²-36=0
onde:
a=4
b=-36
c=0
Δ=b²-4..c
Δ=(-36)²-4.4.0
Δ=1296-16.0
Δ=1296
x=-b+-√Δ/2a
x=+36+-√1296 /2.4
x=36+-36/8=
x1=36+36/8=
x1=9
x2=36-36/8
x2=0
solução: 0,9
b) 7x²-21=0
onde:
a=7
b=0
c=-21
b é igual a zero então :
x1= √3
e
x2= -√3
solução: -√3,√3
beijãoo
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás